Comparação da dose absorvida de dois protocolos de varredura tomográfica em exame de PET/CT (Brazilian Journal of Radiation Sciences (BJRS), 2018)
Positron emission tomography (PET) associated with computed tomography (CT) allows the fusion of functional and anatomical images. When compared with other diagnostic techniques PET/CT subjects the patients to higher radiation dose levels because two radiation modalities in a single exam are used. In this study, the absorbed doses were evaluated in 19 organs from the CT scan. Radiochromic filmstrips were correctly positioned into the Alderson anthropomorphic phantom, masculine version. For this evaluation two Whole-body CT scan protocols were compared, one  protocol for generating images with lower resolution aiming only the anatomical mapping (1), and a second protocol with higher resolution images for diagnostic purposes (2). There was an increase of up to 600 % in the absorbed dose in the hypophysis and cervical spine when comparing the protocols, with an average increase of around 230 % in other organs. The CT organ dose in patients submitted to PET/CT scanning is higher in the protocol used for diagnosis. Considering the higher cost of PET/CT examination and its applications in the diagnosis of minor alterations, in some cases it is necessary that CT scan has diagnostic quality, not only for the anatomical mapping, even knowing the dose increase for the patient. In these cases, the argument for using a higher patient doses technique is based on the Principle of Justification. It is worth emphasizing the importance of a careful evaluation of the need to perform the exam using protocol (2) for all patients, but only in essential cases.